Relação entre a reatividade de pontos de acupuntura e atividade física com afecções ortopédicas determinadas por exames de imagens em equinos - Sousa, Nicole Ruas de [UNESP] (2015)
This study aimed to evaluate the reactivity of acupuncture points by pressure algometer and the relation between physical activity and orthopedic lesions in horses. It was analyzed 116 horses of dressage, racing, polo pony, reproduction/at rest, jumping, work and western performance with lameness confirmed by image diagnosis for reactivity of acupoints with grade 0 when the answer was normal, I, small, II moderate and III, intense, with evasive response, bite or kick, which only II and III were correlated to site of injury by chi square test, and physical activity with type and site of injury by Fisher test. Kruskall-Wallis test was performed, followed by Dunn's test to evaluate the relation between reactivity I, II and III with the pressure algometer. Desmitis were more prevalent in racehorses, western and work, and fractures in racehorses and polo pony. Stifle injuries were more prevalent in dressage than work, shoulder injuries were more prevalente in jumping than work. Hind tendon injuries were less prevalente in jumping than dressage, western and reproduction/at rest. 5336 measurements were performed in 23 bilateral acupoints. The overall mean values pressure algometer was 26 ± 6.43 N and the median corresponding to fingerprints of grades I, II and III were 24, 22 and 20 N, respectively, with significant difference between them, suggesting that palpation has a good correspondence with the pressure algometer to assess the reactivity of acupuncture points. We conclude that there is a relationship between location and type of injury with physical activity and palpation assessment of acupuncture points is helpful in identifying some structures injuries